Evaluation of the revised Nipissing District Developmental Screening (NDDS) tool for use in general population samples of infants and children. Issue 1 (December 2016) - Cairney, John; Clinton, Jean; Veldhuizen, Scott; Rodriguez, Christine; Missiuna, Cheryl; Wade, Terrance; Szatmari, Peter; Kertoy, Marilyn
Abstract Background There is widespread interest in identification of developmental delay in the first six years of life. This requires, however, a reliable and valid measure for screening. In Ontario, the 18-month enhanced well-baby visit includes province-wide administration of a parent-reported survey, the Nipissing District Developmental Screening (NDDS) tool, to facilitate early identification of delay. Yet, at present the psychometric properties of the NDDS are largely unknown. Method 812 children and their families were recruited from the community. Parents (most often mothers) completed the NDDS. A sub-sample (n  = 111) of parents completed the NDDS again within a two-week period to assess test-retest reliability. For children 3 or younger, the criterion measure was the Bayley Scales of Infant Development, 3rd edition; for older children, a battery of other measures was used. All criterion measures were administered by trained assessors. Mild and severe delays were identified based on both published cut-points and on the distribution of raw scores. Sensitivity, specificity, positive and negative predictive values were calculated to assess agreement between tests. Results Test-retest reliability was modest (Spearman's rho = .62, p  < 001). Regardless of the age of the child, the definition of delay (mild versus severe), or the cut-point used on the NDDS, sensitivities (from 29 to 68 %) and specificities (from 58 to 88 %) were poor to moderate. Conclusion The modest test-retest results, coupled with the generally poor observed agreement with criterion measures, suggests the NDDS should not be used on its own for identification of developmental delay in community or population-based settings.